Page Kidney in a Child with Severe Pelviureteric Junction Obstruction - Senthil G. Kamaraj; Ashita Kochunny; Gopinathan Kathirvelu; Praachi Singh; Naeem Samnakay (Case Reports in Urology)
There are various causes of Reno Vascular Hypertension in children reported in the literature. Amongst these, Page kidney gets a rare mention. This phenomenon is a result of the accumulation of blood or urine in the perinephric or subcapsular space, resulting in compression of renal parenchyma, microvascular ischemia, alteration in the renin-angiotensin apparatus, and high renin hypertension. It has been well documented and studied in adults. Only a few cases are reported in the paediatric population. We report a rare presentation of Page kidney in a 5 year 8 months old girl. She initially presented with Dietl’s crisis secondary to left Pelviureteric Junction obstruction (PUJO) causing massive hydronephrosis. She developed Page kidney phenomenon after spontaneous rupture of the pelvicalyceal system formed a tight compressive urinoma. She was managed successfully with internal JJ stenting and ultrasound-guided aspiration of the urinoma followed by elective delayed Pyeloplasty. To our knowledge, this is the first documented case of Page kidney in a child with severe PUJO.